Sosialisasi Pengolahan Sampah dengan Penggunaan Alat Pemotong Ring AMDK Gelas Plastik yang Aman di Bank Sampah SiHatin - Eko Ari Wibowo; Widyastuti Widyastuti; Ida Betanursanti; Dyah Puji Astuti (Lembaga Pengembangan Kinerja Dosen, 2025)
The increase in consumption of plastic bottled drinking water (AMDK) has led to an increase in the amount of plastic waste that requires special handling. One of the main challenges in managing this waste is the process of cutting plastic cup rings, which has been done manually using a cutter or small knife. This manual method is not only less effective but also increases the risk of injury for waste pickers. This research aims to develop a safer and more effective plastic cup ring cutter. Through a socialisation programme and implementation of the tool at Bank Sampah SiHatin, the effectiveness of the tool was tested by comparing the manual method and the use of the cutting tool. The results of the analysis show that the use of this tool is able to increase the cutting speed by 58%, produce more uniform cuts, and eliminate the risk of injury due to the use of cutters. In addition, this tool also improves occupational safety and health (K3) aspects and has a positive impact on the economic value of cutting products. Thus, this innovation is an effective solution in plastic waste management in the informal sector and can be adopted more widely in various other Waste Banks